KRITERIA KEKONVERGENAN CAUCHY PADA RUANG METRIK KABUR INTUITIONISTIC - Muhammad Ahsar Karim; Faisal Faisal; Yuni Yulida (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2012)
In this paper, we construct the Cauchy-convergence criterion in intuitionistic fuzzy metricspace. We start our aim by given the definition of concepts convergence sequence, Cauchysequence, and complete on intuitionistic fuzzy metric space.